Alternative Forms of Tourism: User Generate Content Promote Birdwatching Tourism in Kefalonia Island, Greece - XANTHAKIS, Michail; ANTONOPOULOS, Nikos; KANAVOS, Andreas; KOMNENOU, Anastasia (Journal of Environmental Management and Tourism, 2024)
Kefalonia, an island in the western part of Greece, renowned for its unique geomorphology, lush vegetation, and Mediterranean climate, is an ideal habitat for diverse bird species, making it a prime destination for birdwatching tourism and intercultural communication. This paper harnesses the power of user-generated content (tourists) by systematically collating and analyzing 1,776 ornithological observations recorded online from 1981 to 2018 (human computers and new media). Organized initially using records and further processed with Geographic Information System (GIS) software, the data revealed the presence of 254 bird species across 54 families, with Scolopacidae being the most prevalent. The most frequently sighted species included Lanius senator and Buteo buteo . Notably, Livadi Marsh in Lixouri on the Paliki peninsula emerged as the hotspot with the highest number of observations. This research highlights the rich biodiversity and the critical habitats within Kefalonia Island. The richness of the data collected offers a unique opportunity to understand the dynamics of bird populations over time, examining trends in both common and rare species. The integration of these observations into conservation planning is crucial for targeting efforts that protect vulnerable species and their habitats. This approach not only aids in the preservation of biodiversity but also enriches the global birdwatching community by providing data that supports sustainable birdwatching practices that are sensitive to the ecological needs of observed species.